Neospora caninum and Toxoplasma gondii: Seroprevalence and associated factors in cows from milk farms of Toledo, Parana, Brazil - dos Santos, Joeleni Rosa [UNESP] (2020)
Neospora caninum and Toxoplasma gondii are important protozoa in cattle production. Neosporosis is responsible for reproductive failures in cattle, constituting one of the main causes of abortion and leading to significant economic losses in dairy farming. Toxoplasmosis is a cosmopolitan disease of great importance in the context of public health and animal production. Considering the lack of available data on the subject for the studied region, the objective of the present study was to detect the seroprevalence of antibodies against N. caninum and T. gondii in dairy cows in the municipality of Toledo, Western Paraná, Brazil and to assess how to detect factors associated with risk or protection. Serology was performed with serum samples from 390 dairy cows from 58 farms by indirect immunofluorescence (IFI) reaction using cutoff point 100 for N. caninum and 64 for T. gondii. The analysis of associations between seropositivity and the variables detected in the properties was also performed. The seroprevalence for Neospora caninum was 15.4% (60/390; CI 95% 12.4-19.3) and for Toxoplasma gondii was 38.7% (151/390; CI 95% 34.0-43.6). The prevalence of co-infection was 8.72% (34/390; CI 95% 6.31-11.94). For N. caninum, the presence of abortion was observed as a risk factor (OR= 5.32). With T. gondii, the presence of abortion was found to be a risk factor (OR= 2.09) and properties with 10 or more lactating animals was found to be a protection factor (OR= 0.56). Abortion was also detected as a factor associated with the risk of co-infection (OR= 11.80). Through serological diagnosis, the present study showed that protozoa are widely distributed among dairy cattle in the region, and control and prophylaxis measures should be adopted in the studied animal population. Because abortion is a risk associated with N. caninum, T. gondii, and the two agents surveyed (co-infection), all reproductive disorders detected in cattle should include neosporosis and toxoplasmosis as a differential diagnosis.